ANALISIS GAYA KEPEMIMPINAN KEPALA UPA. PERPUSTAKAAN UNIVERSITAS TANJUNGPURA UNTUK MENGOPTIMALISASIKAN LAYANAN - Inul, Inul; Hanum, Atiqa Nur Latifa; Madeten, Sisilya Saman (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Effective leadership is instrumental in improving employee performance and motivation. The leadership style applied can significantly affect employee performance. Libraries in higher education require a leadership approach that is capable of managing information services optimally. However, there is still a lack of understanding of the most appropriate leadership style to meet the challenges and special needs of their management. This study aims to analyze the leadership style applied by the Head of UPA. Tanjungpura University Library and its impact on employee performance in the service section and its role in increasing employee motivation. The research used qualitative methods with research techniques in-depth interviews with 5 resource persons, non-participatory observation, and documentation. Data analysis techniques use data reduction, data presentation, conclusion drawing, while data validity testing with extended observation, increasing persistence, and triangulation. The results showed that the democratic leadership style applied by the head of the library has a positive influence on employee performance by increasing morale, strengthening participation, improving communication, and opening opportunities for employees to develop professionally. This leadership style also succeeded in increasing employee motivation by involving them in decision making, fostering a sense of responsibility, and strengthening relationships between teams. Proposals to strengthen the practice of democratic leadership is to more actively involve employees in the decision-making process, organizing regular forums or meetings, maintaining open two-way communication, and giving rewards. meetings, maintaining open two-way communication, and rewarding employee contributions